Effect of PyC interphase thickness on mechanical and ablation properties of 3D Cf/ZrC–SiC composite. Issue 11 (15th August 2016) - Yan, Chunlei; Liu, Rongjun; Zhang, Changrui; Cao, Yingbin
Abstract: Three-dimensional (3D) Cf /ZrC–SiC composites were successfully prepared by the polymer infiltration and pyrolysis (PIP) process using polycarbosilane (PCS) and a novel ZrC precursor. The effects of PyC interphase of different thicknesses on the mechanical and ablation properties were evaluated. The results indicate that the Cf /ZrC–SiC composites without and with a thin PyC interlayer of 0.15 µm possess much poor flexural strength and fracture toughness. The flexural strength grows with the increase of PyC layer thickness from 0.3 to 1.2 µm. However, the strength starts to decrease with the further increase of the PyC coating thickness to 2.2 µm. The highest flexural strength of 272.3±29.0 MPa and fracture toughness of 10.4±0.7 MPa m 1/2 were achieved for the composites with a 1.2 µm thick PyC coating. Moreover, the use of thicker PyC layer deteriorates the ablation properties of the Cf /ZrC–SiC composites slightly and the ZrO2 scale acts as an anti-ablation component during the testing.